ENHANCING PGMI STUDENTS’ MOTIVATION AND SELF-CONFIDENCE THROUGH SOCRATIC TEACHING IN FISHBOWL COLLABORATIVE LEARNING - Alam, Muhamad Asruri Faishal; Adi, Banu Setyo Adi; Novianto, Anwar Novianto (Universitas Islam Negeri Mataram, 2026)
This study was motivated by the low levels of learning motivation and self-confidence among PGMI students in Islamic higher education, largely due to the dominance of conventional lecture methods. As prospective primary school teachers, PGMI students are required to develop strong affective competencies to support effective teaching practices. Although the Socratic approach and Fishbowl Discussion have been studied separately, their integration as a structured and sustained pedagogical strategy remains underexplored, particularly in the context of Islamic teacher education in Indonesia. This study aims to examine the effectiveness of Socratic teaching integrated with the Fishbowl Discussion method on students’ learning motivation and self-confidence. A quantitative approach with a one-group pretest–posttest quasi-experimental design was employed. The intervention was conducted over seven meetings, consisting of two introductory sessions and five full implementation sessions. Data were collected through validated questionnaires from 32 PGMI students and analyzed using paired-sample t-tests. The results showed significant improvements in learning motivation (p = 0.001; d = 0.67) and self-confidence (p = 0.003; d = 0.57). These findings demonstrate that the integration of Socratic questioning and Fishbowl Discussion provides an effective and contextually relevant strategy for enhancing affective competencies in prospective primary teacher education.